Controversy and coalition: The new feminist movement across three decades of change - Ferree, Myra Marx; Hess, Beth B. (Routledge, 2000)
Controversy and Coalition is a comprehensive and engaging overview of the American women's movement from the 1960's to the 1990's.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amériques; histoire des femmes*; histoire et politique; militance; mouvements féministes; périodes historiques; ressource en ligne; régions géographiques; thématiques; états-unis